2010
DOI: 10.5155/eurjchem.1.4.282-288.113
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic and thermal characterization of quinoxaline metal complexes

Abstract: KEYWORDSThe coordination behaviour of the quinoxaline ligand with N and O donation sites, derived from 3-(2-oxo-2-p-tolylethyl)quinoxalin-2(1H)-one (HL), towards some transition metal ions namely Mn(II), Fe(III), Co(II), Ni(II), Cu(II) and Zn(II) are reported. The metal complexes are characterized based on elemental analyses, IR, 1 H NMR, solid reflectance, magnetic moment, molar conductance and thermal analyses (TG, DTG and DTA). The ionization constants of the quinoxaline ligand as well as the stability cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Several studies have been described, concerning synthesis and biological activity of a large amount of quinoxalines and 1,4-di-Noxide quinoxaline derivatives, where compounds such as 7-chloro-3-(p-substituted)-phenylaminoquinoxaline-2-carbonitrile-1,4-di-N-oxide, 6,7-dichloro-2-ethoxycarbonyl-3-methylquinoxaline-1,4-di-N-oxide and 3-acetamide-6,7-dichloroquinoxaline-2-carbonitrile-1,4-di-N-oxide derivatives have been shown to possess M. tuberculosis growth inhibition values from 99 to 100% [21,27]. However, it is observed that the lack of the two N-oxide groups lead to the loss of the antimycobacterial activity [27,28].…”
Section: Antitubercular Activitymentioning
confidence: 99%
“…Several studies have been described, concerning synthesis and biological activity of a large amount of quinoxalines and 1,4-di-Noxide quinoxaline derivatives, where compounds such as 7-chloro-3-(p-substituted)-phenylaminoquinoxaline-2-carbonitrile-1,4-di-N-oxide, 6,7-dichloro-2-ethoxycarbonyl-3-methylquinoxaline-1,4-di-N-oxide and 3-acetamide-6,7-dichloroquinoxaline-2-carbonitrile-1,4-di-N-oxide derivatives have been shown to possess M. tuberculosis growth inhibition values from 99 to 100% [21,27]. However, it is observed that the lack of the two N-oxide groups lead to the loss of the antimycobacterial activity [27,28].…”
Section: Antitubercular Activitymentioning
confidence: 99%
“…This in turn, propose tetrahedral geometry for the Co(II) complexes. This is also supported by magnetic moment values (3. ), thus showing their non-electrolytic nature 34 . The magnetic moment values of Co(II) complexes were found in the range of 3.78-3.94 B.M, expected for three unpaired electrons and are in agreement with their tetrahedral geometry 35 .…”
Section: Electronic Spectramentioning
confidence: 99%
“…The electronic spectra of Co(II) complexes generally showed 45 three absorption bands in the region 8650-8790, 17 523-17 800 and 29 805-29 841 cm À1 which may be assigned to 4T 1 g!4T 2 g(F), 4T 1 g!4A 2 g(F) and 4T 1 g!4Tg(P) transitions respectively, and are suggestive of octahedral geometry around the Co(II) ion. The electronic spectral data of Ni(II) complexes showed 46 …”
mentioning
confidence: 99%